2014
DOI: 10.1063/1.4861666
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermal contraction of the first coordination shell in metallic alloy liquids

Abstract: Except for a few anomalous solids and liquids, materials expand upon heating. For liquids, this should be reflected as a shift in the peak positions in the pair correlation function, g(r), to higher r. Here, we present the results of a detailed study of the volume thermal expansion coefficients and the temperature dependences of g(r) for a large number of binary, ternary, and quaternary liquids in the equilibrium and supercooled (metastable liquid below the liquidus temperature) states. The data were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…5a), giving an anomalous negative thermal expansion. Similar behavior has been reported in the first shell of g(r)s that were obtained from experimental measurements [28][29][30]. It appears to be partially the result of an increasing first-shell coordination number with decreasing temperature, leading to a weakening of the bond strengths in the first shell as the valence electrons are shared among more atoms.…”
Section: Resultssupporting
confidence: 71%
“…5a), giving an anomalous negative thermal expansion. Similar behavior has been reported in the first shell of g(r)s that were obtained from experimental measurements [28][29][30]. It appears to be partially the result of an increasing first-shell coordination number with decreasing temperature, leading to a weakening of the bond strengths in the first shell as the valence electrons are shared among more atoms.…”
Section: Resultssupporting
confidence: 71%
“…Specifically, the coordination polyhedron changes to a denser one with a reduced coordination number and a shorter bond length (distance between the center atom and atoms in the first nearest-neighbor shell). In a later report, Gangopadhyay et al 34 also observed similar anomalous shift of the first peak for a number of alloy liquids (but not without obvious exceptions).…”
Section: Introductionmentioning
confidence: 62%
“…An intriguing behavior noticed in recent studies is an anomalous temperature dependence of the first peak position in the atomic PDFs, g(r), of metallic liquids: [33][34][35]71 the position (distance r) corresponding to the maximum intensity of the first peak shifts towards shorter r with increasing temperature (see Fig. 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…expansion, shifting towards larger r with decreasing temperature. This is now emerging as common behavior, reported in many metallic glass-forming liquids [51,52]. The character of the first peak in g(r) for the different glasses is one of the more interesting features (Fig.…”
Section: Resultsmentioning
confidence: 94%